Portuguese landscapes: intensive monocultures and sustainability problems - Almeida, Maria Antónia (ICoWEFS 2021 – International Conference on Water, Energy, Food and Sustainability, 2021)
The Portuguese landscape is the result of thousands of years of human presence. Since the late nineteenth century, when protectionist public policies were put in place to provide for food self-sufficiency, and particularly during the Estado No-vo regime, the use of the land has changed the countryside. The rural exodus of the nineteen sixties resulted in the depopulation of eighty per cent of the Portu-guese territory, where less than twenty per cent of the population now lives. Re-cently there are new trends, based on land concentration, which put the sustaina-bility of the Portuguese rural world at risk. When cultural and natural heritage is being valued as a commercial resource, there is total incompatibility between super intensive monoculture, forest fires and min-ing, and what is advertised for the rural world. Central and local governments’ policies and strategies to reverse rural depopulation are useless when the envi-ronment, the landscape and the quality of life of the population are being endan-gered. Besides the use of chemicals in olive, almond and avocado plantations, dams being drained into irrigation for huge extensions of monocultures and golf courses, there is landscape devastation, the social issue of precarious seasonal la-bour, the plastic pollution of greenhouses. There is a lot to debate on the sustain-ability of these plantations, the production of food and the excessive use of water in times of draught and the prospect of desertification of the Portuguese southern lands.